Mercury concentrations and stable isotope ratios (δ13C and δ15N) in pelagic nekton assemblages of the south-western Indian Ocean. (January 2022) - Annasawmy, Pavanee; Point, David; Romanov, Evgeny V.; Bodin, Nathalie
Abstract: Mercury (Hg) concentrations and stable isotope values (δ 13 C and δ 15 N) were investigated in micronekton collected from La Pérouse and MAD-Ridge seamounts, Reunion Island and the southern Mozambique Channel. Organisms occupying epipelagic habitats showed lower Hg concentrations relative to deeper dwelling benthopelagic ones. Increasing Hg concentrations with increasing body size were recorded in the Mozambique Channel and Reunion Island. Positive relationships were observed between Hg levels and δ 15 N values in pelagic nekton assemblages collected at MAD-Ridge seamount and the southern Mozambique Channel, suggesting biomagnification of Hg. Concentrations of Hg in organisms across the south-western Indian Ocean were within the same range of values. Total Hg concentrations depend on a range of factors linked to habitat range, body size and trophic position of the individuals. To our knowledge, this is the first study investigating the patterns of Hg concentrations in pelagic nekton assemblages from the south-western Indian Ocean. Highlights: Mercury concentrations were relatively homogeneous across the study sites. Epipelagic organisms showed lower Hg concentrations than deeper dwelling benthic ones. Mercury concentrations may increase with increasing body size of individuals. Larger-sized nektonic species have high trophic positions and Hg burdens.